In situ antimony doping of solution-grown ZnO nanorods - Briscoe, Joe; Gallardo, Diego E.; Dunn, Steve (Royal Society of Chemistry, 2009)
ZnO nanorods are doped with Sb during the aqueous chemical synthesis by addition of Sb acetate dissolved in ethylene glycol. The reliable production of p-type ZnO has been a challenge for some time. This is because the as-grown ZnO is nominally n-type due to intrinsic defects, 1 so holes introduced by acceptor dopants are generally compensated by the high intrinsic free electron density. Despite these diﬃculties, there have been increasing examples in recent years of p-type ZnO thin films and nanostructures. There is significant interest in producing p-type ZnO nanostructures due to many potential device applications. For example, transistors or diodes based on ZnO nano-homojunctions could be used for transparent electronics, UV optoelectronics and photonic